The Ma'na Maghza's Approach to Self-Healing Verses in the Qur'an - Hakim, Lukman (ojs.unsiq.ac.id, 2024)
Cases of self-injury continue to increase year after year. In Indonesia - based on the Basic Health Research (Riskesdas) in 2018 - indicates that 19 million people aged 15 and above experience mental illness. Thus, this study aims to explain some self-healing techniques in the Qur'an as a solution to the occurrence of these cases and so that we keep mentally healthy. This research is pursued with the Ma'na cum Maghza approach, which is a method of interpreting the Qur'an by exploring the historical meaning and developing the meaning to the meaning of significance (maghza) to be applied in contemporary times. This study found that in Q.S al-Ankabut [29]: 45, the terms